The effects of hardware acceleration on power usage in basic high-performance computing - Amsler, Christopher (Kansas State University, 2012)
Power consumption has become a large concern in many systems including portable electronics and supercomputers. Creating efficient hardware that can do more computation with less power is highly desirable. This project proposes a possible avenue to complete this goal by hardware accelerating a conjugate gradient solve using a Field Programmable Gate Array (FPGA). This method uses three basic operations frequently: dot product, weighted vector addition, and sparse matrix vector multiply. Each operation was accelerated on the FPGA. A power monitor was also implemented to measure the power consumption of the FPGA during each operation with several different implementations. Results showed that a decrease in time can be achieved with the dot product being hardware accelerated in relation to a software only approach. However, the more memory intensive operations were slowed using the current architecture for hardware acceleration.
Keywords: Field programmable gate array; Power; High performance computing; Hardware acceleration; Computer Engineering (0464); Electrical Engineering (0544)